2012
DOI: 10.1097/imi.0b013e31827439ea
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Image Guidance Improves Navigation for Beating Heart Mitral Valve Repair

Abstract: Objective Emerging off-pump beating heart valve repair techniques offer patients less invasive alternatives for mitral valve (MV) repair. However, most of these techniques rely on the limited spatial and temporal resolution of transesophageal echocardiography (TEE) alone, which can make tool visualization and guidance challenging. Methods Using a magnetic tracking system and integrated sensors, we created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Within healthcare, ARAs have been developed to train or educate medical professionals [21], as a navigation tool during surgical procedures [22, 23] to enhance visualization at the operating room [24] and as a therapeutic tool in the treatment of patients [25–27]. …”
mentioning
confidence: 99%
“…Within healthcare, ARAs have been developed to train or educate medical professionals [21], as a navigation tool during surgical procedures [22, 23] to enhance visualization at the operating room [24] and as a therapeutic tool in the treatment of patients [25–27]. …”
mentioning
confidence: 99%
“…Essential components that are prerequisite for establishing a simulation-based learning curriculum include having appropriate infrastructure, protected time for both trainees and teachers, regular simulation participation distributed over time, and a validated method to monitor performance (McGaghie et al, 2011;Gardner et al, 2015;Andersen et al, 2018). Simulation technology has been applied in many surgical disciplines as an adjunct to clinical training, using a variety of component task trainers, animal tissue-based simulators, and computer-aided simulation models (Friedl et al, 2002;Gallagher et al, 2004;Aggarwal et al, 2006;Chu et al, 2012;Trehan et al, 2014;Liu et al, 2015;Valdis et al, 2015Valdis et al, , 2016Mafeld et al, 2017;Korzeniowski et al, 2018;Ruikar et al, 2018;Patel et al, 2019). Cadaveric simulation has likewise been utilized in several non-thoracic specialties, with varying degrees of sophistication, whole body or component parts, and on occasion in combination with another model (Jackson et al, 2003;Güvençer et al, 2007;Ghanem et al, 2013;Carey et al, 2014;Ahmed et al, 2015;Benet et al, 2015;Egle et al, 2015;Camp et al, 2016;Sharma et al, 2016;Burns et al, 2017;Robinson et al, 2017;Willaert et al, 2018;Yiasemidou et al, 2018;Zada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of this guidance system for mitral valve repair, we found that simply defining the valve annuli from tracked TEE was sufficient for image guidance and eliminated the need for complex preoperative models and registrations with associated errors. 14,15 Using this guidance system, the surgeon can easily and intuitively identify the tool, surgical targets, and high-risk areas.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous work using AR and TEE for beating heart mitral valve repair has found that simply defining the valve annuli from tracked TEE is sufficient for image guidance. 14,15 This eliminates the need for complex preoperative models and registrations with associated errors. 16,17 We have adopted this AR and TEE guidance system for TAVI deployment.…”
mentioning
confidence: 99%